2006
DOI: 10.1021/bi051972s
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured RNA Is a Substrate for tRNase Z

Abstract: tRNase Z, which exists in almost all cells, is believed to be working primarily for tRNA 3' maturation. In Escherichia coli, however, the tRNase Z gene appears to be dispensable under normal growth conditions, and its physiological role is not clear. Here, to investigate a possibility that E. coli tRNase Z cleaves RNAs other than pre-tRNAs, we tested several unstructured RNAs for cleavage. Surprisingly, all these substrates were cleaved very efficiently at multiple sites by a recombinant E. coli enzyme in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
21
1
Order By: Relevance
“…7A that had 3 or 4 residues removed. These data confirm the conclusions of Shibata et al (20) that the enzyme can act as an endoribonuclease.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…7A that had 3 or 4 residues removed. These data confirm the conclusions of Shibata et al (20) that the enzyme can act as an endoribonuclease.…”
Section: Resultssupporting
confidence: 92%
“…These data were confirmed by experiments showing that RNase BN processed tRNA precursors lacking (15,16) or containing (8,19) the 3Ј-terminal CCA sequence in vivo. Other recent experiments showed that the E. coli enzyme could also act on some unstructured, synthetic RNAs, although most of these studies were carried out at 52°C (20). To examine in more detail the catalytic potential of RNase BN, we have carried out a systematic analysis of substrate specificity using a variety of defined, synthetic RNAs that enabled us to study separately various structural parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PhnP does exhibit regiospecific activity against 2Ј,3Ј-cyclic nucleotides. The E. coli tRNase ZipD is not active against 2Ј,3Ј-or 3Ј,5Ј-cyclic nucleotides (10) but will cleave short sequences of unstructured RNA (44). The noncatalytic Zn 2ϩ binding site of PhnP is one of the striking features of this structure, which, intriguingly, is shared by another "accessory" protein, PqqB, of the pyrroloquinoline quinone biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%